Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1074/jbc.m006947200
|View full text |Cite
|
Sign up to set email alerts
|

Processing of β-Secretase by Furin and Other Members of the Proprotein Convertase Family

Abstract: The amyloid peptide is the main constituent of the amyloid plaques in brain of Alzheimer's disease patients. This peptide is generated from the amyloid precursor protein by two consecutive cleavages. Cleavage at the N terminus is performed by the recently discovered ␤-secretase (Bace). This aspartyl protease contains a propeptide that has to be removed to obtain mature Bace. Furin and other members of the furin family of prohormone convertases are involved in this process. Surprisingly, ␤-secretase activity, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
198
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(217 citation statements)
references
References 36 publications
(55 reference statements)
16
198
1
Order By: Relevance
“…Retrieval of furin from endosomal to TGN compartments was also shown to be dependent on phosphorylation/dephosphorylation of its cytoplasmic domain (45). Therefore, the subcellular localization of BACE is regulated in a remarkably similar fashion like furin, a protease that has recently been demonstrated to be required for propeptide cleavage of BACE (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrieval of furin from endosomal to TGN compartments was also shown to be dependent on phosphorylation/dephosphorylation of its cytoplasmic domain (45). Therefore, the subcellular localization of BACE is regulated in a remarkably similar fashion like furin, a protease that has recently been demonstrated to be required for propeptide cleavage of BACE (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…BACE is cotranslationally modified by N-glycosylation and further maturates by complex glycosylation as well as proteolytic removal of its prodomain by a furin-like protease (11)(12)(13)(14). The majority of BACE molecules are localized within Golgi and endosomal compartments, where they colocalize with ␤APP (4,5,7,12,14).…”
mentioning
confidence: 99%
“…During maturation, BACE1 undergoes a number of post/co-translational modifications, including N-glycosylation, disulfide bridge formation, and palmitoylation (Bennett et al 2000b;Capell et al 2000;Huse et al 2000;Benjannet et al 2001). The propeptide of immature BACE1 is removed by Furin and related proteases during maturation (Capell et al 2000;Creemers et al 2001). Surprisingly, the propeptide seems not to significantly affect BACE1 proteolytic function (Creemers et al 2001).…”
Section: Subcellular Sites Of App Processingmentioning
confidence: 97%
“…The propeptide of immature BACE1 is removed by Furin and related proteases during maturation (Capell et al 2000;Creemers et al 2001). Surprisingly, the propeptide seems not to significantly affect BACE1 proteolytic function (Creemers et al 2001). BACE1 reaches the PM and becomes enriched in lipid rafts (Riddell et al 2001;Cordy et al 2003).…”
Section: Subcellular Sites Of App Processingmentioning
confidence: 99%
“…Recent studies revealed that BACE is synthesized as an immature and inactive form in the endoplasmic reticulum [11], and undergoes maturation during its transport to cell surface along the secretory pathway [12][13][14][15][16]. The mature BACE is then internalized from cell surface to endosomes [3,12], followed by sorting to the trans golgi network (TGN) for recycling or to lysosomes for degradation [15,16].…”
Section: Introductionmentioning
confidence: 99%